‘The right to (decent) work. The right to everyone or “chosen” ones?’ The situation in Poland - Ludera-Ruszel, Agata (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2021)
Work represents a particular economical, social and psychological relevance to the worker. Because of a personal dimension of work, that involves human beings, it cannot be separated from workers. The approach to human labour as not a market product, but as a human being, is contained in the statement that ‘labour is not a commodity’, firstly expressed in the International Labour Organization’s 1944 Declaration of Philadelphia. The reference to this assumption more recently on the occasion of the 100th anniversary of ILO activities clearly evidence that the history of labour has come full circle and the idea of decent work for workers has returned to being the centre of labour law regulations. The concerns relating to the inadequate protection of workers coincided in time with the transformative change in the world of work. With this in mind, it is then worth considering more deeply whether a decent job is an ‘exclusive’ and ‘luxurious’ ideal, and leave outside its scope a number of workers who are in need of protection because of their unique situation. The position of Poland in this picture will be analysed.